Effectiveness of word of mouth marketing in company’s sales performance in the fast food industry: The case of chef’s pride – restaurant Dar es salaam - Ndutu, Fatuma (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University in partial fulfillment of the requirement for the award of Master of Business Administration in Corporate Management (MBA-CM) Mzumbe University